Impact of trade facilitation on intra-manufacturing export among ECOWAS member states - Adeyinka, Olure-Bank; Muktar, Mustapha; Zakaree , Saheed; Abraham, Alexander; Yakubu, Alfa (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
This study investigates the effects of trade facilitation policies on intra-manufacturing exports among ECOWAS member states. Utilizing the Generalized Method of Moments (GMM) linear model, this research analyzes data from 2015–2020 for the ECOWAS member states. The findings reveal that trade facilitation policies in the ECOWAS region fall below the global average. This discrepancy is primarily due to the extensive bureaucratic processes in the region, leading to increased costs for exporting and importing goods. Consequently, there is a significant need for trade facilitation to enhance intra-manufacturing exports within ECOWAS. Based on these insights, the study recommends several policy interventions to improve trade flow and bolster intra-manufacturing exports in the ECOWAS region. These include a stronger commitment to trade agreements among ECOWAS member states, the adoption of information and communication technology (ICT) to streamline trade processes and reduce bureaucratic delays associated with document processing for exports and imports, the strengthening of institutional frameworks within the member states, and the formulation of policies aimed at increasing industrialization levels to enhance manufacturing exports throughout the ECOWAS region.